Δ-Tocotrienol suppresses tumorigenesis by inducing apoptosis and blocking the COX-2/PGE2 pathway that stimulates tumor–stromal interactions in colon cancer. (August 2017) - Wada, S.; Naito, Y.; Matsushita, Y.; Nouchi, M.; Kawai, M.; Minami, E.; Aoi, W.; Ikeda, S.; Higashi, A.; Yoshikawa, T.
Highlights: δ-Tocotrienol-rich diet suppressed colorectal cancer in a mouse model. δ-Tocotrienol showed the most significant anti-cancer effect in colon cancer cells. δ-Tocotrienol induced apoptosis by stimulating caspase-3 and caspase-9. δ-Tocotrienol affected cancer stromal cells by reducing COX-2 protein expression. Abstract: Anticancer effects of δ-tocotrienol have been reported for several types of cancer, but have not been fully elucidated in colorectal cancer. We investigated the anti-proliferative effect of tocotrienols in vitro, in colon epithelial cells and stromal cells, and in vivo, in an induced colorectal cancer mouse model. Of the four isoforms tested, δ-tocotrienol exerted the most potent anti-proliferative effect on colon adenocarcinoma cells. δ-Tocotrienol reduced the nitrite and prostaglandin E2 (PGE2 ) concentrations in mouse embryonic fibroblasts (MEFs) pretreated with δ-tocotrienol and stimulated with lipopolysaccharide (LPS) and interferon γ. Furthermore, supernatants of LPS-stimulated MEFs promoted adenocarcinoma cell proliferation, while δ-tocotrienol treatment suppressed this effect. Additionally, a δ-tocotrienol-enriched diet significantly suppressed tumor formation in azoxymethane and dextran sulfate sodium-treated mice. Taken together, these data suggest that a δ-tocotrienol-enriched diet prevents colorectal cancer. At the molecular level, tocotrienols exert a direct anti-proliferative effect on colon adenocarcinoma cells, and an indirect, stromal cell-mediated, anti-proliferative effect.